In Memoriam: Dionisio José Herrera Guibert - Ferran Martinez Navarro (University of New South Wales, 2019)
Dr Dionisio Herrera Guibert, who passed away on 4-12-2018, was a key figure in the development of the epidemiology training, both in Spain and internationally. This commentary is in his memory and recognises his achievements in field epidemiology.